Sitting, standing and moving during work and leisure among male and female office workers of different age: a compositional data analysis - Elin Johansson; Svend Erik Mathiassen; Charlotte Lund Rasmusse; David M. Hallman (BMC, 2020)
Abstract Background Gendered patterns of physical activity behaviours may help explaining health inequalities between men and women. However, evidence on such patterns in the working population is sparse. This study aimed at documenting and comparing compositions of sitting, standing and moving at work and during leisure among male and female office workers of different age. Methods Sitting (including lying), standing and moving were measured using accelerometry for, on average, four working days in 55 male and 57 female Swedish office workers. Behaviours were described in terms of time spent in four exhaustive categories: sitting in short (< 30 min) and long (≥30 min) bouts, standing, and moving. In a compositional data analysis approach, isometric log-ratios (ilr) were calculated for time sitting relative to non-sitting, time in short relative to long sitting bouts, and time in standing relative to moving. Differences between genders (men vs. women), domains (work vs. leisure), and according to age were examined for each ilr using ANOVA. Results At work, time spent sitting in short bouts, sitting in long bouts, standing, and moving was, on average, 29, 43, 21 and 7% among men, and 28, 38, 26 and 7% among women. Corresponding proportions during leisure were 34, 27, 27 and 13% among men and 28, 27, 32 and 13% among women. Men spent more time sitting relative to non-sitting ( η p 2 $$ η_p^2 $$ =0.04, p = 0.03) than women, and less time standing relative to moving ( η p 2 $$ η_p^2 $$ =0.07, p = 0.01). At work compared to during leisure, both genders spent more time sitting relative to non-sitting ( η p 2 $$ η_p^2 $$ =0.47, p < 0.01); within sitting more time was spent in long relative to short sitting bouts ( η p 2 $$ η_p^2 $$ =0.26, p < 0.01), and within non-sitting, more time was spent standing than moving ( η p 2 $$ η_p^2 $$ =0.12, p < 0.01). Older workers spent less of their non-sitting time moving than younger workers ( η p 2 $$ η_p^2 $$ =0.07, p = 0.01). Conclusion Male office workers spent more time sitting relative to non-sitting than female workers, and more time moving relative to standing. Both genders were sitting more at work than during leisure. Older workers moved less than younger. These workers could likely benefit from interventions to reduce or break up prolonged sitting time, preferably by moving more.